A MANAJEMEN PERUBAHAN PENDIDIKAN KARAKTER PADA PESERTA DIDIK - Wongarso, Silviana Winty (Satya Widya, 2021)
Character education has long been imparted on people, both at home and in school, as well as in society. In today's world, character education is critical for human life, particularly for the next generation of the nation. Character education in children has begun to fade as the times have progressed. Therefore, character education is critical to be applied to students in schools. The purpose of this study is to determine how the management of character education changes students at SD Negeri 1 Klopoduwur. The researcher used a qualitative method with a semi-structured interview with the Principal of SD Negeri 1 Klopoduwur. Character education experienced by these students underwent a significant change, which at first could be said to have faded, but can now be replanted in various existing ways, and students accept it well, and can be applied in everyday life in an environment where they live, as well as with support from family and the surrounding community.